A progressive damage fatigue model for unidirectional laminated composites based on finite element analysis: theory and practice - M. Hack; D. Carrella-Payan; B. Magneville; T. Naito; Y. Urushiyama; W. Yamazaki; T. Yokozeki; W. Van Paepegem (Fracture and Structural Integrity)
The simulation of the fatigue damage of laminated composites under multi-axial and variable amplitude loadings has to deal with several new challenges and several methods of damage modelling. In this paper we present how to account for the complex loading by using the damage hysteresis operator approach for fatigue. It is applied to a fatigue model for intra-laminar damage based on stiffness degradation laws from van Paepegem [1]and has been extended to deal with unidirectional carbon fibres. The parameter identification method is presented here and parameter sensitivities are discussed. The initial static damage of the material is accounted for by using the Ladevze damage model and the permanent shear strain accumulation based on Van Paepegems formulation. This approach has been implemented into commercial software. The intra-laminar fatigue damage model combines efficient methods with a low number of tests to identify the parameters of the stiffness degradation law, this overall procedure for fatigue life prediction is demonstrated to be cost efficient at industrial level